A Case of a Gastrointestinal Stromal Tumor Diagnosed at the Postpartum Period - Sefa Kurt; Aras Emre Canda; Emre Karadeniz; Tugba Yavuzsen; Ozgul Sagol; Funda Obuz; Mehmet Serefettin Canda (Case Reports in Obstetrics and Gynecology)
Introduction. We discuss a rare gastrointestinal stromal tumor (GIST) case detected at the 10th postpartum week and we want to pay attention to the challenges and improvements in the diagnosis, surgery, chemotherapy, and follow-up of this rare tumor accompanied with the review of the current literature. Case Presentation. A 32-year-old multiparous woman presented with abdominal swelling 10 weeks after her second vaginal birth. Abdominal examination revealed a mass starting from the pelvic level and extending to the right upper quadrant. Radiological examinations showed a solid, multiloculated, and hypervascular mass starting from the pelvis and extending to the transverse colon. En bloc mass with a 20 cm jejunal segment resection and a left pelvic side wall peritonectomy with omentectomy was performed. The pathologic examination revealed a high-risk GIST which originated from the jejunum and disseminated to the peritoneum. The patient has been given imatinib 400 mg/day since then. She did not reveal any progression during the 15-month follow-up postoperatively. Conclusion. GIST tumors are rare and there is not sufficient information in the literature regarding its management. In this patient having high risk GIST and GIST sarcomatosis we successfully treated the patient by surgery and adjuvant imatinib chemotherapy.